Silica coating application on heat-cured acrylic resin plates towards the surface hardness and the amount of residual monomers - Suhono, Rosa Sharon; Wahyuningtyas, Endang; Ismiyati, Titik (Padjadjaran Journal of Dentistry, 2019)
Introduction: Silica has been used as a coating material on acrylic resin denture plates to reduce the attachment of C. albicans, and acrylic resin denture coating application has been shown to increase the resistance. Acrylic resin as denture plate has many advantages, including good aesthetical aspect, easy to be manipulated, and relatively low costs. Acrylic resin also has disadvantages, namely the presence of residual monomers, low abrasion resistance, and broken easily. Residual monomers have poor biocompatibility and can weaken the mechanical strength of acrylic resin dentures. The purpose of this study was to analyse the silica coating application on heat-cured acrylic resin plates towards the surface hardness and the amount of residual monomers. Methods: This study used as much as 40 rod-shaped heat-cured acrylic resin specimens measured 13 x 13 x 2 mm. Specimens were divided into 2 groups (n = 20), namely the control group and the acrylic resin plate group applied with silica coating. Specimens in the treatment group applied with silica coating material using the dip-coating method. The surface hardness was tested using the Vickers hardness tester, and the amount of residual monomers was tested using gas chromatography. All data were analysed using an independent t-test. Results: Surface hardness in the group applied with silica coating was significantly higher than the control group (p < 0.05), while the remaining monomers of acrylic resin plate specimens in the group applied with silica coating were significantly lower than the control group (p < 0.05). Conclusion: Silica coating increases the surface hardness and decreases the amount of residual monomer of heat-cured acrylic resin.Keywords: Silica coating, surface hardness, residual monomer, acrylic resin